2007
DOI: 10.1080/00140130601068683
|View full text |Cite
|
Sign up to set email alerts
|

Mild body cooling impairs attention via distraction from skin cooling

Abstract: Many contemporary workers are routinely exposed to mild cold stress, which may compromise mental function and lead to accidents. A study investigated the effect of mild body cooling of 1.0 degree C rectal temperature (Tre) on vigilance (i.e. sustained attention) and the orienting of spatial attention (i.e. spatially selective processing of visual information). Vigilance and spatial attention tests were administered to 14 healthy males and six females at four stages (pre-immersion, deltaTre = 0, -0.5 and - 1.0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 16 publications
0
20
1
Order By: Relevance
“…Exposure to moderate cold thermal environment was found to decrease the reaction time and executive function (Muller et al 2012;Spitznagel et al 2009;Mäkinen, Palinkas, et al 2006;Adam et al 2008), and decreasing in attention (Spitznagel et al 2009;Mäkinen, Palinkas, et al 2006;Adam et al 2008;Cheung, Westwood, and Knox 2007;Muller et al 2011;Hartley and MCcabe 2001). The cognitive working performances experimented by included articles are shown in the One study found that cognitive dysfunctions persist for some time after the cold exposure and despite the stabilization of the core and skin temperature and thermal sensation (Muller et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to moderate cold thermal environment was found to decrease the reaction time and executive function (Muller et al 2012;Spitznagel et al 2009;Mäkinen, Palinkas, et al 2006;Adam et al 2008), and decreasing in attention (Spitznagel et al 2009;Mäkinen, Palinkas, et al 2006;Adam et al 2008;Cheung, Westwood, and Knox 2007;Muller et al 2011;Hartley and MCcabe 2001). The cognitive working performances experimented by included articles are shown in the One study found that cognitive dysfunctions persist for some time after the cold exposure and despite the stabilization of the core and skin temperature and thermal sensation (Muller et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A predominance of skin temperature effects has also been reported with respect to the disrupting effect of body cooling on performance. For example, Cheung et al [17] administered vigilance and spatial attention tests while subjects were immersed in a cool water bath and reported that all disruptive effects on performance occurred immediately with skin cooling, while performance did not get any worse with the much slower developing decline in core body temperature. Of note, studies like these differ with respect to the applied temperature range.…”
Section: Support For An Effect Of Skin Temperature On Vigilance In Humentioning
confidence: 99%
“…Importantly, decreased attention is also one of the leading causes of automotive accidents. Cheung, Westwood, and Knox, (2007) found that skin temperature cooling impaired attention by acting as a distractor, and cooling core body temperature did not further impair cognitive performance. Additionally, research by Muller et al (2011) showed that using exercise to increase body core temperature during cold stress did not improve attention while the participants were subjected to a cold environment, once again due to distraction.…”
Section: Cold Stress and Cognitive Performancementioning
confidence: 96%